CP-053 Identification of a national portfolio of unlicensed pharmaceutical preparations in denmark. (24th March 2015) - Villesen, CT; Schmidt, AMS; Jensen, L; Herkell, K; Iversen, J; Andersen, L; Nørregaard, S; Elsner, D
Abstract : Background: In Denmark, hospital pharmacies manufacture as well as buy unlicensed pharmaceutical preparations prescribed by physicians. Each Danish hospital pharmacy is responsible for manufacturing and supplying preparations within their own Region; however cross-Regional coordination is limited. This has resulted in a vast portfolio of unlicensed pharmaceutical preparations with possibly many duplications and similar preparations and with different or unknown clinical use, even though the clinical needs are similar throughout the country. Purpose: To identify a common national portfolio corresponding to clinical need by analysing and categorising the use of unlicensed pharmaceutical preparations from all Danish hospital pharmacies. Material and methods: The study was a retrospective analysis of sales data from 2012 and 2013, which were collected from the electronic system of all Danish hospital pharmacies. The total sales data were analysed by 6 clinical pharmacists representing all major hospital pharmacies. The process was facilitated by a project manager. The clinical pharmacists categorised the existing portfolio according to preparation, formulation and indication. They identified identical preparations, alternatives and estimated the overall clinical relevance. The pharmacists consulted colleagues, physicians and guidelines to ensure broad and accepted categorization. Results: A total of 2, 754 unlicensed pharmaceutical preparations were identified in the existing portfolio. Of these, 739 preparations were considered to be of clinical relevance and should be included in the updated national portfolio of unlicensed pharmaceutical preparations. Indications were allocated to all 739 preparations. Conclusion: A national portfolio of extemporaneous pharmaceutical preparations with corresponding indications was identified. The portfolio helps secure a unified content and use of unlicensed pharmaceutical preparations across Denmark, which potentially could lead to increased patient safety. References and/or Acknowledgements: 1Martin Høj, Emendo A/S No conflict of interest.